Can mining promote industrialization? A comparative analysis of policy frameworks in three Southern African countries - Judith Fessehaie; Zavareh Rustomjee; Lauralyn Kaziboni (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper explores the potential to leverage large-scale mineral extraction in Botswana, Zambia, and Zimbabwe to foster mineral beneficiation and upstream industries. The evidence suggests that the success or failure of a resource-based industrialization approach is country and sector specific, requiring the deployment of different and appropriately tailored policy instruments. We also find that the design and implementation of resource-based industrialization policies is heavily influenced by power relationships, in terms of control over mining rents, relationships between mining companies and domestic business, and across different segments of the domestic business sector.
Keywords: L5; L6; O1; O25; 330; linkage development; supplier development; beneficiation; Southern Africa; resource-based industrialization